Etude Comparative de la Capacite de Travail Aerobie et Anaerobie Alactique Selon les Postes Occupes Chez les Footballeurs: Le Cas des Champions d’Afrique L’E.S. Sétif Saison Sportive 2014/2015 - Bensalem, Salem; Mohmed, Hobara; Rachid, Menella (جامعة عبد الحميد بن باديس مستغانم - معهد التربية البدنية والرياضية, 2020)
The aim of our study was to provide a comparative analysis of the basic physical qualities in football, namely Endurance and Speed according to the positions occupied in the field. As part of our study, 24 players from the ESS (Entente de Sétif African Champion) in the senior category underwent two educational tests: The Gacon. G 45''15 '': VMA and VO2max) and 30 meters speed the results of our research have shown that there are significant differences at p <0.05 concerning aerobic capacities VMA and VO2max in favour of midfield players is better than that of attackers and defenders. On the other hand there are no significant differences concerning the quality of speed of the players of the three compartments (Defense; Midfielder and Attack).
Keywords: القدرات الهوائية -- لاعبو كرة القدم -- البطولات الرياضية -- بطولة إفريقيا